2011
DOI: 10.1158/0008-5472.can-11-1059
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells in Squamous Cell Carcinoma Switch between Two Distinct Phenotypes That Are Preferentially Migratory or Proliferative

Abstract: Epithelial-to-mesenchymal transition (EMT) is an important driver of tumor invasion and metastasis, which causes many cancer deaths. Cancer stem cells (CSC) that maintain and initiate tumors have also been implicated in invasion and metastasis, but whether EMT is an important contributor to CSC function is unclear. In this study, we investigated whether a population of CSCs that have undergone EMT (EMT CSCs) exists in squamous cell carcinoma (SCC). We also determined whether a separate population of CSCs that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
345
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(375 citation statements)
references
References 31 publications
19
345
0
11
Order By: Relevance
“…Biddle et al (39) demonstrated that self-renewing CSCs in squamous cell carcinoma contained two biologically distinct phenotypes as follows: a population of CSCs that had undergone EMT (EMT CSCs), and a separate population of CSCs that had retained their epithelial characteristics (non-EMT CSCs). Their experiments revealed that the EMT and non-EMT CSCs are switchable (39). We observed in this study that SP fractions of both Has2 ϩNeo and Has2 ⌬Neo cells contained a significant number of CD44 high /CD24 low cells.…”
Section: Coordinated Roles Of Snail and Twist In Has2-induced Csc Expsupporting
confidence: 54%
“…Biddle et al (39) demonstrated that self-renewing CSCs in squamous cell carcinoma contained two biologically distinct phenotypes as follows: a population of CSCs that had undergone EMT (EMT CSCs), and a separate population of CSCs that had retained their epithelial characteristics (non-EMT CSCs). Their experiments revealed that the EMT and non-EMT CSCs are switchable (39). We observed in this study that SP fractions of both Has2 ϩNeo and Has2 ⌬Neo cells contained a significant number of CD44 high /CD24 low cells.…”
Section: Coordinated Roles Of Snail and Twist In Has2-induced Csc Expsupporting
confidence: 54%
“…Furthermore, recent studies show that the bipotent CSCs in breast and squamous cell carcinoma often co-express both epithelial and mesenchymal markers [54,55] (see detailed discussion in the electronic supplementary material, §5). These results support our prediction that hybrid E/M cells can gain stemness.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified an association between CSCs and the EMT, with evidence suggesting that cells undergoing the EMT acquire stem cell-like traits (32)(33)(34). Furthermore, CSCs exhibit a mesenchymal-like appearance in immortalized, non-tumorigenic mammary epithelial cells and breast cancer (33).…”
Section: Discussionmentioning
confidence: 99%